Suitability of TCLP for cement-based products - Shen, Aldwin Weishun. (2008)
The impact of rapid industrialization and urbanization in the world resulted in an explosive increase in waste generation and has since become a serious problem in many countries. Among the many budding solutions, the stabilization/solidification (S/S) technology and the reuse of its products for civil engineering applications are gaining increasing popularity. The U.S. EPA Toxicity Characteristics Leaching Procedure (TCLP) is one of the most commonly used leach test to study the leaching behavior of solidified wastes in landfills. When TCLP is used with cement-based waste forms, however, there may be a problem that the acid neutralizing capacity (ANC) of such waste can neutralize the acidity of the leachant rendering the true assessment of leaching potential impractical. This is particularly important for the assessment of the long term leaching characteristic after the ANC of the waste is exhausted. This project aims to study the suitability of TCLP to assess the leaching performance of cement-based S/S waste products. The aspect of primary investigation is the effect of loss of ANC, and the resulting change in pH, on the measured heavy metal concentration in the solution. The investigations were carried out through exploring modified test procedures from the TCLP. The modified leach tests are mTCLP, pTCLP and mEP.